Climate warming causes mast seeding to break down by reducing sensitivity to weather cues. (4th March 2021) - Bogdziewicz, Michał; Hacket‐Pain, Andrew; Kelly, Dave; Thomas, Peter A.; Lageard, Jonathan; Tanentzap, Andrew J.
Abstract: Climate change is altering patterns of seed production worldwide with consequences for population recruitment and migration potential. For the many species that regenerate through synchronized, quasiperiodic reproductive events termed masting, these changes include decreases in the synchrony and interannual variation in seed production. This breakdown in the occurrence of masting features harms reproduction by decreasing the efficiency of pollination and increasing seed predation. Changes in masting are often paralleled by warming temperatures, but the underlying proximate mechanisms are unknown. We used a unique 39‐year study of 139 European beech ( Fagus sylvatica ) trees that experienced masting breakdown to track the seed developmental cycle and pinpoint phases where weather effects on seed production have changed over time. A cold followed by warm summer led to large coordinated flowering efforts among plants. However, trees failed to respond to the weather signal as summers warmed and the frequency of reproductive cues changed fivefold. Less synchronous flowering resulted in less efficient pollination that further decreased the synchrony of seed maturation. As global temperatures are expected to increase this century, perennial plants that fine‐tune their reproductive schedules based on temperature cues may suffer regeneration failures. Abstract : Climate change is altering patterns of seed production with consequences for population recruitment and migration. We used a 39‐year study of European beech that experienced masting break‐down to track the seed developmental cycle and pinpoint phases where weather effects on seed production have changed over time. A cold followed by warm summer led to coordinated flowering efforts among plants. However, trees failed to respond to the weather signal as summers warmed and the frequency of reproductive cues changed fivefold. As global temperatures are expected to increase, plants that fine‐tune their reproductive schedules based on temperature cues may suffer regeneration failures.